TRIGENERATION AS A WAY OF ENERGY EFFICIENCY IMPROVEMENT REVIEW ARTICLE - T. V. Pantsyrnaya (Real Economics Publishing House, 2014)
The overview of current scientific literature on one of the key aspects of the development of the energy sector is presented, it is the increase of the efficiency of energy systems. The ability of cogeneration and trigeneration systems to increase energy efficiency of power stations, supermarkets, shopping centers, airports, etc. was demonstrated. In addition, it was shown that these systems have a high potential for reducing greenhouse gas emissions. The examples of polygeneration systems and ways to optimize them by improving techno-economic parameters were also demonstrated.